"Aint Justice Wonderful" The Chicago Tribune's Battle of Midway Story and the Government's Attempt at an Espionage Act Indictment in 1942. (March 2014) - Sweeney, Michael S.; Washburn, Patrick S.
This monograph examines the government's only attempt to prosecute a member of the mainstream press, the Chicago Tribune, for an alleged violation of the Espionage Act in World War II stemming from the newspaper's front-page account of the Battle of Midway. Although other historians have investigated this case, this monograph draws on never-before-seen documents in eleven archives as well as documents released by the Federal Bureau of Investigation (FBI), Justice Department, and Navy in response to Freedom of Information Act requests to provide the fullest account of how the story came to be published and how and why the government decided to seek a grand jury indictment. The prosecution of the Tribune tested the limits of press freedom in wartime, provided an inside look at military censorship and the ethics of war correspondents, and showed the extreme eagerness of President Roosevelt to go after Robert McCormick's newspaper.